Glocal Arabic online: The case of 3arabizi - Bianchi, Robert Michael (Studies in Second Language Learning and Teaching, 2012)
The term glocal has been used to describe phenomena that simultaneously blend both global and local elements (see Featherstone, Lash, & Robertson, 1995, p. 101). Nowhere is this more evident than in the existence of 3arabizi, itself a blended language composed of English and Vernacular Arabic, written in Latin letters but using arithmographemes, that is, numerals as letters to represent hard-to-transliterate sounds because they do not exist in English (see Bianchi, 2012).1 As part of a doctoral study investigating online language choice involving Arabic and English, this paper examines the unique stylistic and topical functions of 3 arabizi when compared with its linguistic forbears, that is, Arabic and English in a multilingual web forum. The findings indicate that 3arabizi is used for more informal, intimate and phatic communication than either Arabic or English, though these latter two languages or codes are not entirely formal in form and purpose either.